2018
DOI: 10.1016/j.artd.2017.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Empiric treatment is less costly than Staphylococcus aureus screening and decolonization in total joint arthroplasty patients

Abstract: The aim of our study was to compare the cost of preoperative empiric mupirocin treatment of all total joint arthroplasty patients with a standard Staphylococcus aureus screening and decolonization protocol. The cost of empiric mupirocin treatment is $24.65 per patient, whereas the cost of a standard S. aureus screening and decolonization protocol is $60.32 per patient. Given that more than 1,051,000 total joint arthroplasties are performed annually, the cost savings with empiric treatment is nearly $40 million… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 11 publications
0
7
0
1
Order By: Relevance
“…This methodology has been shown to be the most cost-effective approach in reducing SSIs as compared with the standard screening and treatment strategies. [23][24][25][26] Additionally, this method helps reduce confusion for false negative or positive results as well as streamlines the presurgical process. Courville et al found that both treat-all and screen and treat strategies in TKA and THA were cost effective compared with no treatment and the cost-effectiveness ratios between the treat all and screen and treat strategies were similar with trivial cost differences.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This methodology has been shown to be the most cost-effective approach in reducing SSIs as compared with the standard screening and treatment strategies. [23][24][25][26] Additionally, this method helps reduce confusion for false negative or positive results as well as streamlines the presurgical process. Courville et al found that both treat-all and screen and treat strategies in TKA and THA were cost effective compared with no treatment and the cost-effectiveness ratios between the treat all and screen and treat strategies were similar with trivial cost differences.…”
Section: Discussionmentioning
confidence: 99%
“…21 22 Multiple protocols for addressing and treating nasal carriage of S. aureus have been evaluated with various financial implications and recommendations. 23 24 25 26 27…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, mupirocin ointment at 1928.3 yen/product is needed to implement UD for all patients when including personnel costs. In the United States, Stirton et al reported the cost of empiric treatment with mupirocin for all patients as an estimated $24.65 per patient (equivalent to 2711.5 yen at 110 yen to 1 US Dollar), which included the personnel costs for instruction on mupirocin application [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, mupirocin ointment at 1641.3 yen/product is needed to implement UD for all patients and this excludes personnel costs. In the United States, Stirton et al reported the cost of empiric treatment with mupirocin for all patients as an estimated $24.65 per patient (equivalent to 2711.5 yen at 110 yen to 1 US Dollar), which included the personnel costs for instruction on mupirocin application [19].…”
Section: Discussionmentioning
confidence: 99%